4CPS-247 Local assessment of the impact of pharmacist-led medication reconciliation on hospitalised elderly patients. (March 2019) - Nobili, S; Campbell Davies, SE; Galfrascoli, E; Tinelli, C; Picca, M; Marino, P; Muserra, G; Medaglia, M
Abstract : Background: Medication reconciliation (MR) through pharmacists' interventions (PIs) is a standardised practice in many countries to reduce drug-related problems (DRPs), such as drug-drug interactions, no therapeutic indication and inappropriate duplications. DRPs, which are relatively common in poly-treated elderly hospitalised patients, can increase morbidity and healthcare costs. In Italy, MR has still not been systematically introduced, therefore, local assessments are crucial to evaluate feasibility. Purpose: To evaluate the impact of pharmacist-led MR. Material and methods: A pre-post intervention study was performed including hospitalised poly-medicated patients>65 years: in the pre-intervention group (PRE-group) MR was not conducted (May to September 2017); and in the post-intervention (POST-group) pharmacist-led MR was performed (November 2017 to March 2018). Data, collected with a specifically designed MR form from medical records and the hospital database, were registered in an Excel database including: patient demographics, number of prescriptions and DRPs at admission and at discharge, number of PIs and clinician acceptance rate in the POST-group and rehospitalisation rate 3 months after discharge in both groups. Statistical analysis was performed using STATA 15. Students t -test for independent data was used to compare quantitative variables between the two groups, while the Chi-square test was used for qualitative variables. Results: A total of 84 patients were included: 34 in the PRE-group (35.3% male, mean age 84.5±6.7, mean number of prescriptions per patient on admission 7.4±2.7, at discharge 8.0±2.6) and 50 in the POST-group (45.1% male, mean age 83.2±17.5, mean number of prescriptions per patient on admission 8.4±3.2, at discharge 7.7±3.0). DRPs at discharge were substantially reduced after the implementation of MR conducted by a pharmacist (p<0.001): in the PRE-group, mean 2.90±2.83 DRPs per patient were identified on admission and 3.79±2.99 at discharge, while in the POST-group 4.80±2.97 DRPs per patient on admission and 2.64±1.75 at discharge leading to a significant difference in terms of reduction of DRPs at discharge between the two groups (p<0.05). In total, 288 PIs were performed with a 74% clinician acceptance rate. The rehospitalisation rate reduced significantly in the POST-group (35% vs 10%, p<0.05). Conclusion: Results showed pharmacist-led MR to be an effective procedure in the local setting, reducing DRPs and rehospitalisations in elderly patients. Therefore, MR programmes should be introduced into Italian standard practice to reduce healthcare costs. References and/or acknowledgements: None. No conflict of interest.